Differences in regional development on the territory of the Republic of Serbia - Živanović, Zora; Gatarić, Dragica R. (Bulletin of Geography. Socio-economic Series, 2017)
Unbalanced regional development is one of the basic characteristics of the regional development of the Republic of Serbia. The aim of the paper is to highlight the proportions of unbalanced regional development of Serbia by positioning regions in accordance with the values of the indicators included in the survey: population density, (un)employment (the number of employed people per 1,000 inhabitants), activity structure and the amount of average income per employee. The indicators presented in the paper emphasize the role of certain regions in the current regional reality of Serbia. Also, they exemplify regional disparities more comprehensively in terms of the achieved level of socio-economic development and the orientation of the analysed regions to particular sectors of the economy.